Increasing Exposed Metal Site Accessibility in a Co-MOF-74 Material With Induced Structure-Defects - Villajos, Jose A.; Jagorel, Noëmie; Reinsch, Stefan; Emmerling, Franziska (Frontiers in Materials, 2019)
Metal-organic frameworks (MOFs) are promising nanoporous materials with many practical applications. This owes largely to their remarkable porosity and the presence of specific chemical functionalities, such as exposed metal sites (EMS). The MOF-74 structure is known for exhibiting one of the highest EMS densities among porous materials. Moreover, the inclusion of structural defects has been proposed to enhance activity further. This was previously achieved by mixing the original linker together with a second, having lower topology. The presence of structural defects was evidenced by the resulting crystalline properties and thermal stability. In this work, different mixtures of tetratopic 2,5 dihydroxyterephthalic acid with up to 60 % of the tritopic hydroxyterephtalic acid were used to synthesize crystalline Co-MOF-74-like materials. Materials synthesized from higher proportions than 30 % of hydroxyterephtalic acid in the synthesis media collapse upon partial removal of the solvent molecules. This indicates the presence of structural defects and the importance of the solvent molecules in stabilizing the crystalline structures. Electron microscope images show that crystal size reduces with inclusion of hydroxyterephtalic acid as the second linker. The presence of coordinated solvent molecules at the EMS was evaluated by FTIR spectroscopy, so that a higher degree of solvent-exchange was observed during washing for defective structures. Furthermore, TG analysis suggests defective structures exhibit lower desolvation temperatures than the defect-free structures. Finally, N2 adsorption-desorption analesis at -196 °C showed an enhanced accessibility of the gas to the inner porosity of the defective structures and therefore, the EMS of the material. All these finding make this pathway interesting to enhance the potential interest of these materials for an industrial application because of both a facilitated activation and a better access to the active sites.